2018
DOI: 10.7150/ijbs.24546
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 induces autophagy-mediated cell death via NOS2 signaling in human bronchial epithelium cells

Abstract: The biggest victim of ambient air pollution is the respiratory system. Mainly because of the harmful components, especially the particulate matters with an aerodynamic diameter of ≤ 2.5µm (PM2.5), can be directly inhaled and deeply penetrate into the lung alveoli, thus causing severe lung dysfunction, including chronic cough, bronchitis and asthma, even lung cancer. Unfortunately, the toxicological mechanisms of PM2.5 associations with these adverse respiratory outcomes have still not been clearly unveiled. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 34 publications
1
41
0
4
Order By: Relevance
“…A previous study indicated that PM2.5 activated a number of apoptosis pathways in human epithelial lung cells (L132) in culture (9). PM2.5 also induced autophagy-mediated cell death via NOS2 signaling in human bronchial epithelium cells (33). The direct toxic effect of PM2.5 on human umbilical vein endothelial cells provides a novel insight into the mechanism of cardiovascular diseases caused by PM2.5 exposure (34).…”
Section: Discussionmentioning
confidence: 95%
“…A previous study indicated that PM2.5 activated a number of apoptosis pathways in human epithelial lung cells (L132) in culture (9). PM2.5 also induced autophagy-mediated cell death via NOS2 signaling in human bronchial epithelium cells (33). The direct toxic effect of PM2.5 on human umbilical vein endothelial cells provides a novel insight into the mechanism of cardiovascular diseases caused by PM2.5 exposure (34).…”
Section: Discussionmentioning
confidence: 95%
“…It has been widely reported that exposure to PM2.5 for a long time can be consistently correlated with a high mortality rate due to the components of PM2.5 consisting of nitrogen dioxide (NO 2 ) and SiO 2 . PM2.5 induces the expression of nitric oxide synthase 2 (NOS2) and subsequently generates NO, which elevates excessive autophagic effects . Furthermore, PM2.5 could accelerate the apoptotic response of airway epithelial cells in the pathogenesis of COPD .…”
Section: Discussionmentioning
confidence: 99%
“…PM and O 3 exposure can regulate autophagy. 125,202,[210][211][212][213] Whether effects of pollutant exposure on autophagy alter coronavirus assembly and replication is unknown (Fig. 2).…”
Section: Pollutant Exposure Interferes With Mitochondrial Function Anmentioning
confidence: 99%